Dynamiczne Zagadnienia Ciał o Własnościach Lepko-Sprężystych - Olesiak, Z. (Engineering Transactions, 1961)
This is a survey written with the purpose of completing the analogous survey written by R. M. DAVIES, [53], and H. KOLSKY, [54]. In particular, it includes monographs and textbooks published in recent years (items [43] to [52]) and original works of Polish authors. The mathematical description of the problem is discussed as well as the methods of solving theoretical problems of viscoelastic bodies.